Exon, intron and splice site locations in the spliceosomal B complex - Wolf, Elmar (Nature Publishing Group, 2009)
In recent years, electron microscopy (EM) has allowed the generation of three-dimensional structure maps of several spliceosomal complexes. However, owing to their limited resolution, little is known at present about the location of the pre-mRNA, the spliceosomal small nuclear ribonucleoprotein or the spliceosome's active site within these structures. In this work, we used EM to localise the intron and the 5′ and 3′ exons of a model pre-mRNA, as well as the U2-associated protein SF3b155, in pre-catalytic spliceosomes (i.e. B complexes) by labelling them with an antibody that bears colloidal gold. Our data reveal that the intron and both exons, together with SF3b155, are located in specific regions of the head domain of the B complex. These results represent an important first step towards identifying functional sites in the spliceosome. The gold-labelling method adopted here can be applied to other spliceosomal complexes and may thus contribute significantly to our overall understanding of the pre-mRNA splicing process.